Inhalational burns in children - Whitelock-Jones, Linda (Division of Paediatric Surgery, 2017)
This study began in 1990 in the Burn Unit of The Red Cross War Memorial Children's Hospital (RCWMCH) in Capetown. It came to our attention that children in the Burn Unit developed respiratory problems. These were complications of fireburns, smoke inhalation, explosions and even hot water scalds. They presented with a wide and confusing array of symptoms and many failed to improve with the symptomatic treatment given. Greater understanding of the pathology was needed in order to investigate and manage these problems correctly. The ultimate aim of this study was to establish a treatment protocol that could be followed by junior staff.